Pearls and pitfalls in musculoskeletal imaging : variants and other difficult diagnoses - Bennett, D. Lee; El-Khoury, Georges Y. (Cambridge medicine, 2013)
Presents over 90 musculoskeletal conditions which can commonly cause confusion and mismanagement in daily radiological practice.